The power of controversy: authenticity and offensiveness perceptions - Limbeck, Miriam Muriel (2022)
Consumers increasingly demand companies to take a stand on controversial socio-political debates, but the consequences of engaging in such controversies remain insufficiently documented. This research shows that controversy in brands leads to both increased offensiveness and decreased authenticity, both linked to decreased purchase intention. Political orientation moderated perceptions of authenticity in controversial brands: When participants on the political right agreed with the controversy, they perceived the controversial brand as more authentic. On the left, agreement with the controversy ledto decreased authenticity. Additionally, splitting countries into collectivist vs. individualistic societies partly explained the differing perceptions of offensiveness in controversial brands.